2020
DOI: 10.1001/jama.2020.3980
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Concern—Possible Reporting of the Same Patients With COVID-19 in Different Reports

Abstract: , JAMA and the JAMA Network journals have received hundreds of manuscripts and direct queries related to coronavirus disease 2019 (COVID-19), including research reports, case series and case reports, and opinion pieces. The editors have become aware that some of the patients described in some of these manuscripts, sometimes with overlapping authorship, have been reported in more than 1 submission. This inclusion of the same patients in more than 1 report has not been clearly indicated in the submitted manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 2 publications
0
107
0
2
Order By: Relevance
“…Circumvention of usual research steps (delay of IRB approval [71], inclusion of same patients in several studies); 2) Limited peer-review process (the usual due diligence from editors and reviewers is sidestepped, potentially leading to unnoticed errors in data and calculations, incomplete reporting of methods and results, as well as underestimation of study limitations); 3) Increased potential for publication bias (in the interest of showing promising data and in the race to achieve recognition, there may be added inclination to publish positive results and disregard negative ones). The extent and impact of these considerations remain currently uncertain but were acknowledged in the development of this guideline.…”
Section: Discussionmentioning
confidence: 99%
“…Circumvention of usual research steps (delay of IRB approval [71], inclusion of same patients in several studies); 2) Limited peer-review process (the usual due diligence from editors and reviewers is sidestepped, potentially leading to unnoticed errors in data and calculations, incomplete reporting of methods and results, as well as underestimation of study limitations); 3) Increased potential for publication bias (in the interest of showing promising data and in the race to achieve recognition, there may be added inclination to publish positive results and disregard negative ones). The extent and impact of these considerations remain currently uncertain but were acknowledged in the development of this guideline.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some evidence suggests misleading duplicate reporting 11 and other problems with patient data handling that can be easily overlooked due to absence of information on data gathering and processing. We consider this especially problematic as robust patient data could provide some answers on potential efficacy of repurposing widely available drugs 12 or important risk factors 13 that could potentially save thousands of lives in the upcoming days.…”
Section: Discussionmentioning
confidence: 99%
“…Using meta-analysis to explore clinical determinants for death of COVID-19 patients has been a problem due to insufficient sample size and overlapped cases [1]. In the study, we re-analyzed the largest confirmed case series reported publicly by the Chinese center for disease control and prevention (44,672 laboratory confirmed cases updated through February 11, 2020, [2]), to explore the clinical risk factors associated with death.…”
mentioning
confidence: 99%